Channels and Marketing Margins of Tuna (Euthynnus Sp) Catches of Fishermen in Karangasem District, Karangasem Regency, Bali - Ni Ketut Puspita Sari; Dewa Nyoman Sadguna; I Gusti Ngurah Sugiana (Warmadewa University Press, 2019)
This study aims to examine the forms of marketing channels and assess the value of marketing margins at each marketing institution involved in the marketing process of fishing tuna caught in Karangasem District, Karangasem Regency, Bali. This study uses a survey method using a questionnaire tool. Sampling techniques for fishermen have used proportional random sampling techniques or sample selection based on certain elements and categories while for intermediary traders and consumers the snowball sampling method, or the method of taking samples from a population. Data analysis was performed descriptively and cost margin analysis. The results showed that there were 4 marketing channels for tuna fish caught by fishermen in Karangasem Subdistrict, Karangasem Regency, Bali, namely marketing channel I from Fishermen to Retailers to Final Consumers with a margin of Rp.1,500 where retailers bought at Rp.2,000 then sold to consumers for Rp.3,500 marketing channel II from fishermen to brokers to collectors to processors to stall traders and to end consumers with a margin of Rp.4.131 marketing channel III from fishermen to brokers to collectors to market traders to stall traders to end consumers with a margin of Rp.3.131 marketing channel IV from fishermen to brokers to collectors to market traders to consumers with a margin of Rp.2,131. Marketing margins in each marketing channel, namely in the marketing channel I retailer margin Rp.1,500. In the marketing channel II, the middleman received a margin of Rp.681 collectors Rp.200- processing Rp.1,500, and stall traders Rp.1,750. In channel III the middleman gets a margin of Rp.681 collectors Rp.200 market traders Rp.750 and at the level of a stall trader Rp.1,500. In channel IV the middleman gets a margin of Rp.681 at the level of collectors Rp.200 at the market trader level Rp.1,250. From the four channels, it is known that the largest margin distribution is at retailers reaching 100 percent and the smallest margin distribution at collectors reaches 4.8 percent. This is driven by the desire to seek high profits at a small cost